Effect of a Brief Supportive and Educational Intervention on the Psychological Well-Being of Mothers with Babies in Neonatal Wards of a Tertiary Hospital in Ibadan, Nigeria. (20th May 2021) - Oyekunle, Olufemi O; Bella-Awusah, Tolulope; Ayede, Adejumoke I; Omigbodun, Olayinka O; Ani, Cornelius C
Abstract: OBJECTIVE: To assess the effect of a supportive educational intervention on the psychological wellbeing of mothers whose babies were admitted to Neonatal Care Unit (NCU) in Nigeria. METHODS: Controlled trial involving 41 mothers whose babies were consecutively admitted into two NCUs (21 in the intervention group and 19 controls). The intervention group received two group-based sessions which included psychological coping strategies, and familiarity with NCU environment, equipment, personnel and procedures. The control group received usual care. Outcome measures were depressive symptoms (Edinburg Postnatal Depression Scale—EPDS), stress-related to NCU (Parental Stressor Scale: Neonatal Intensive Care Unit—PSS: NICU) and post-traumatic symptoms (Impact Event Scale-Revised—IES-R). RESULTS: Difference-in-Differences (DiD) analysis showed a difference of −4.70 in PSS: NICU score in favour of the intervention group which was statistically significant [ F (3, 75) = 9.47, p  < 0.0001, R 2 = 0.28]. The differences in EPDS (0.91) and IES-R (2.55) were not statistically significant [ F (3, 75) = 10.10, p  = 0.74] and [ F (3, 75) = 10.13, p  = 0.73], respectively. All the mothers in the treatment group expressed satisfaction with the intervention. CONCLUSION: This brief group-based supportive educational intervention for mothers with babies in NCU was feasible, acceptable and helpful in reducing stress related to NCU. Larger controlled trials are recommended to establish the generalizability of these findings in this region. LAY SUMMARY: Babies born too early and or with complications require admission to special hospital called Neonatal Care Unit (NCU) to help them to survive. However, parents whose babies are admitted to NCU can find the experience frightening. We examined how to reduce the fear and stress mothers in Nigeria experience when their babies are admitted to NCU. We had two groups of mothers. The first group made up of 21 mothers was taught how to cope with the stress of having a baby in NCU. They were also shown how the various equipment in the NCU work, what the staff in NCU do and what types of things need to be done to help their babies. The second group of 19 mothers received usual care but did not have the extra teaching the first group received. After 2 weeks, we checked the level of depression and stress the mothers in both groups had compared with the level before the first group received the extra teaching. We found that mothers in the first group who received the extra teaching were less stressed about having their babies in the NCU compared with the mothers that did not receive the teaching.